Salts of amino acids : crystallization, structure and properties - Fleck, Michel (Springer International Publishing, 2014)
This book is about amino acid salts and presents comprehensive data, including crystallographic parameters in easily accessible tables, for quick identification. The work describes amino acids and their salts with cations, anions and compounds from a chemical, physical and crystallographical point of view: crystal structures, molecular structures and polymorphs are explored. Readers will find additional data on structural properties, crystal growth, and the relation of structure and physical properties of amino acid salts. This work covers a wide range of relevant topics, from the discovery of important ferroelectrics or non-linear optical materials, to nutrients, flavor enhancers or drugs. Apart from their biological function, this family of organic compounds has been employed in the synthesis of a vast variety of salts. Common mistakes and pitfalls in research on amino acid salts are explained so that the reader can avoid them, and numerous figures are included to provide a visual overview of structural aspects of amino acid salts. Since amino acids have been found to be of importance in many fields, this work will appeal across the sciences. Amino acids and their salts have an impact on materials science and on pharmaceutical and physics research, whilst professional practitioners in the fields of chemistry and food science will also find this work and the data presented here of value.